A Mendelian locus on chromosome 16 determines susceptibility to doxorubicin nephropathy in the mouse - Zheng, Zongyu (National Academy of Sciences, 2005)
The development of kidney disease is influenced by both genetic and environmental factors. Searching for models of glomerulopathy that display strong gene–environment interaction, we examined the determinants of anthracycline-induced nephropathy, a classic, strain-dependent experimental model applied to rodents in the past four decades. We produced three crosses derived from mice with contrasting susceptibility to doxorubicin (DOX) nephropathy and, surprisingly, we found that this widely studied model segregates as a single-gene defect with recessive inheritance. By genome-wide analysis of linkage, we mapped the trait locus to chromosome 16A1-B1 (DOXNPH locus) in all three crosses [peak logarithm of odds (lod) score of 92.7, P = 1 × 10(-65)]; this interval represents a susceptibility locus for nephropathy. Gene expression analysis indicated that susceptibility alleles at the DOXNPH locus are associated with blunted expression of protein arginine methyltransferase 7 (Prmt7) on chromosome 8, a protein previously implicated in cellular sensitivity to chemotherapeutic agents (lod = 12.4, P = 0.0001). Therefore, Prmt7 expression serves as a molecular marker for susceptibility to DOX nephropathy. Finally, increased variation in the severity of kidney disease among affected mice motivated a second genome-wide search, identifying a locus on chromosome 9 that influences the severity and progression of nephropathy (DOXmod, peak lod score 4.3, P = 0.0018). These data provide genetic and molecular characterization of a previously unrecognized Mendelian trait. Elucidation of DOX nephropathy may simultaneously provide insight into the pathogenesis of renal failure and mechanisms of cytotoxicity induced by chemotherapeutic agents.